1996
DOI: 10.1177/0265407596133009
|View full text |Cite
|
Sign up to set email alerts
|

Felt Obligation Towards Parents in Mexican-American and Anglo-American Young Adults

Abstract: The present study compares self-reports of felt obligation towards parents, cultural attitudes about family functioning and perceptions of family interactions in a sample of 100 Mexican-American and Anglo-American young adults. On average, Mexican-American men and women reported significantly higher levels of familism, more collectivist attitudes and more helping behavior in relationships with parents than did Anglo-Americans, while Anglo respondents reported having more contact with social systems outside the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 26 publications
4
97
4
Order By: Relevance
“…For example, research has shown that Mexican Americans value "simpatía" more strongly than Anglo-Americans do (Marín & Marín, 1991). Furthermore, Mexican Americans tend to be more collectivist than European Americans (Freeberg & Stein, 1996). Why then do Americans and bilinguals using English score higher in Extraversion, Agreeableness, and Conscientiousness than Mexicans and bilinguals using Spanish?…”
Section: Article In Pressmentioning
confidence: 99%
“…For example, research has shown that Mexican Americans value "simpatía" more strongly than Anglo-Americans do (Marín & Marín, 1991). Furthermore, Mexican Americans tend to be more collectivist than European Americans (Freeberg & Stein, 1996). Why then do Americans and bilinguals using English score higher in Extraversion, Agreeableness, and Conscientiousness than Mexicans and bilinguals using Spanish?…”
Section: Article In Pressmentioning
confidence: 99%
“…The two items are summed to create a scale for traditional gender attitudes (Cronbach's alpha=.53), and a higher score indicates less acculturation to the U.S. Literature on Mexican-American culture indicates that immigrants tend to hold traditional views about gender roles and that these views may alter over time in the U.S. (Freeberg and Stein 1996;Gil and Vega 1996;Rogler and Cooney 1984;Sabogal et al 1987). …”
Section: Variablesmentioning
confidence: 99%
“…On self-description tasks, participants generate more aspects of their individual self than their collective self regardless of levels of collectivism and individualism (Gaertner et al, 1999, Investigation 4;Ybarra & Trafimow, 1998, Experiment 3) and culture of origin (Trafimow et al, 1991). Furthermore, persons of color (i.e., African Americans, Asian Americans, and Latinos) score higher than do Anglos on measures of collectivism, yet they score just as high as Anglos on measures of individualism (Freeberg & Stein, 1996;Gaines et al, 1997).…”
Section: The Universality Of Individual-self Primacy: Culture As a Momentioning
confidence: 99%